Indexing authenticity: sociolinguistic perspectives - Lacoste, Véronique; Leimgruber, Jakob; Breyer, Thiemo (Linguae & litterae, 2014)
Authenticity : a view from inside and outside sociolinguistics / Véronique Lacoste, Jakob Leimgruber and Thiemo Breyer -- Language, society and authenticity : themes and perspectives / Nikolas Coupland -- The trouble with authenticity / Penelope Eckert -- Chinese social practice and San Franciscan authenticity / Lauren Hall-Lew -- Being more alternative and less Brit-pop : the quest for originality in three urban styles in Athens / Lefteris Kailoglou -- "100% authentic Pittsburgh" : sociolinguistic authenticity and the linguistics of particularity / Barbara Johnstone -- 'Oh boy, ¿hablas español?' - Salsa and the multiple value of authenticity in late capitalism / Britta Schneider -- The commodification of authenticity / Monica Heller -- The race from place : dialect eradication vs. the linguistic "authenticity" of terroir / Michael Silverstein -- Reported speech as an authentication tactic in computer-mediated communication / Graham M. Jones -- Authenticity in dialect performance? A case study of "cyber-Jamaican" / Andrea Moll -- From vernacular to digital ethnolinguistic repertoire : the case of Nigerian Pidgin / Theresa Heyd and Christian Mair -- Hybridity as authenticity in Nigerian hip-hop lyrics / Akinmade T. Akande -- Authentic writing / Florian Coulmas -- Lexical variation at the internationalized university : are indexicality and authenticity always relevant? / Anna Kristina Hultgren -- "Real communities", rhetorical borders : authenticating British identity in political discourse and on-line debate / Martin Gill -- What's in a promesse authentique? Doubting and confirming authenticity in 17th-century French diplomacy / Johanna Sprondel and Tilman Haug
Keywords: Aufsatzsammlung; Konferenzschrift; Soziolinguistik; Index; Authentizität